Software development rhythms : harmonizing agile practices for synergy - Lui, Kim Man.; Chan, Keith C. C. (Hoboken, N.J. : Wiley-Interscience, 2008)
An accessible, innovative perspective on using the flexibility of agile practices to. increase software quality and profitability. When agile approaches in your organization don't work as expected or you feel. caught in the choice between agility and discipline, it is time to stop and think about. software development rhythms!. Agile software development is a popular development process that continues to reshape philosophies on the connections between disciplined processes and agile practices. In Software Development Rhythms, authors Lui and Chan explain how adopting one practice and combining.
SOFTWARE DEVELOPMENT RHYTHMS; CONTENTS; PREFACE; Special Acknowledgment; Part I: Essentials; 1 NO PROGRAMMER DIES; 2 UNDERSTANDING PROGRAMMERS; 3 START WITH OPEN SOURCE; Part II: Rhythms; 4 PLAGIARISM PROGRAMMING; 5 PAIR PROGRAMMING; 6 REPEAT PROGRAMMING; 7 AGILE TEAMING; 8 INCREMENTAL DESIGN; 9 TEST-DRIVEN DEVELOPMENT; EPILOGUE: MEDLEY; INDEX.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
John Wiley and Sons
Keywords: Computer software -- Development; COMPUTERS -- Programming -- Open Source; COMPUTERS -- Software Development & Engineering -- Tools; COMPUTERS -- Software Development & Engineering -- General; Computer software -- Development